Water purification using cellulosic fibers extracted from agriculture wastes and their modified copolymers - Rabab M. Nasser; Maid A. Siddiq; Fakhra J. Jamil (Kuwait Journal of Science)
The scarcity of water limits individuals' capacity to engage in fundamental activities. The objective of this study is to investigate the creation of novel cellulosic fibers derived from peanut shells, utilizing varying concentrations of alkaline solutions and different temperatures. These fibers are subsequently transformed into cellulose acetate (CA). To further enhance sustainability, the prepared CA is copolymerized with polyethylene terephthalate (PET) obtained from recyclable water bottles. The resulting material is then fabricated into fibers using an electrospinning instrument. The chemical composition of the synthesized compounds is analyzed through Fourier-transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). The thermal stabilities of the fibers are assessed via Thermal gravimetric analysis (TGA) and derivative thermogravimetry (DTG). Additionally, the effectiveness of the fabricated fibers as water filters is evaluated, demonstrating high efficiency in this regard.